2007
DOI: 10.1177/030802260707000205
|View full text |Cite
|
Sign up to set email alerts
|

Making a Difference, Teamwork and Coping: The Meaning of Practice in Acute Physical Settings

Abstract: Occupational therapists in acute physical settings face challenges and tensions between their holistic professional values and the often reductionist focus of their work. A hermeneutic phenomenological investigation explored the meaning of practice for nine occupational therapists in an acute National Health Service trust in England. Semi-structured interviews were analysed using a framework for interpretive analysis of phenomenological data. Critical reflective evaluation enables readers to judge the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The timeliness of home assessments in the discharge process was raised as a concern by Robertson and Finlay (). Therapists reported feeling under pressure to complete home assessments urgently to continue the rapid throughput of clients.…”
Section: Resultsmentioning
confidence: 99%
“…The timeliness of home assessments in the discharge process was raised as a concern by Robertson and Finlay (). Therapists reported feeling under pressure to complete home assessments urgently to continue the rapid throughput of clients.…”
Section: Resultsmentioning
confidence: 99%
“…Bridging the gap between hospital and home is basic to the occupational therapy role in acute care practice and crucial to safe discharge (35), so assessment processes must ensure that this role is carried out successfully. Providing the means to identify the environmental difficulties that impose restrictions for clients is crucial to problem-solving (35).…”
Section: Assessment Of the Home Environmentmentioning
confidence: 99%
“…Providing the means to identify the environmental difficulties that impose restrictions for clients is crucial to problem-solving (35). Therefore assessment processes need to allow for developing rapport with clients to ensure effective identification of home-based problem areas.…”
Section: Assessment Of the Home Environmentmentioning
confidence: 99%
“…Occupational therapists have also indicated that hospital work environments tend to favour reductionist practices that are in tension with the profession's commitment to holistic and person-centred approaches and values (ROBERTSON;FINLAY, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Occupational therapists' views about their work in hospitals frequently express concerns about being devalued or disregarded by the other members of the health team, and a lack of understanding about their professional roles (ATWAL, 2002;GALHEIGO;TESSUTO, 2010;GRIFFIN;MCCONNELL, 2001;ROBERTSON;FINLAY, 2007). Wilding andWhiteford (2007, 2008) have also noted occupational therapists' difficulties in explaining their unique and valuable contributions in hospital contexts.…”
Section: Literature Reviewmentioning
confidence: 99%